The collective witness - Witherington III, Ben; (1951-...) (U.S.A, 2010)
In this book, Ben Witherington III explains the theological and ethical significance of Christ as the center of the New Testament. He explains how each New Testament writer's encounter with Christ changed not only his worldview, but also his understanding of moral living. But in contrast to much of contemporary scholarship, Witherington believes the New Testament writers are not writing conflicting or competing theologies. He suggests they are different voices singing the same chorus. Witherington explores historical and ideological perspectives as they influence our apprehension of the New Testament. This text does not provide a list of legalistic moral commands to follow, but it does provide insight on controversial subjects, such as divorce, homosexuality and gender roles.
Keywords: Bible -- New Testament -- Criticism, interpretation, etc